The health status of hybrid grouper Epinephelus fuscoguttatus (♀) x E.lanceolatus (♂) cultured in floating-net cage at Kelapa Dua Island, Seribu Islands, Indonesia - Ruku Ratu Borut; Sukenda; Sri Nuryati; kukuh Nirmala; Irzal Effendi; Widanarni (Jurnal Akuakultur Indonesia)
This study aimed to identify the fish health status, based on the total erythrocytes (cells/mm3), total leukocytes (cells/mm3), hemoglobin level (g %), hematocrit, and histopathological profiles. This study was performed on February, 2021 – January, 2022. The study was located in floating-net cage of Kelapa Dua Island, Seribu Islands, Jakarta, Indonesia. Sampling was performed by a purposive-sampling method, environmental parameter measurements, containing temperature and salinity, clinical symptom observation in fish, total erythrocytes, leukocytes, hemoglobin, hematocrit, histopathological profiles of hybrid grouper liver and kidney, and existence of VNN virus. The observation results present the behavior changes in sick fish, namely whirling on the net cage surface, dead-sleeping or death-like condition below the net cage. Hybrid grouper has total erythrocytes of 1.36 x 106 – 5.13 x 106 cells/mm3, total leukocytes of 2.9 x 104 – 7.9 x 104 cells/mm3, hemoglobin level of 5.56 - 10.94 g %, and hematocrit of 13.31 - 24.78 %. From the histopathological observation, hepatocyte, necrosis, vacuolysis was occurred in liver and tubular, leukocyte infiltasi, nicrosis was occurred in kidney and with the highest prevalence of VNN at 20 – 80 %. Therefore, hybrid grouper is sick due to increased number of leukocytes at 5.13 x 106 cells/mm3 above the normal range, followed by decreased hemoglobin and hematocrit levels at 5.56 - 10.94 g % and 13.31 - 24.78 %, respectively, due to organ damage.